Analisis Alur Cerita Dalam Dongeng Princess 5 Benua Sebagai Alternatif Bahan Pembelajaran Menceritakan Kembali Peristiwa Dalam Teks Fiksi untuk Siswa Kelas V Sekolah Dasar - Widjojoko, Widjojoko; Wardana, Deni; Annisa, Ajeng (Universitas Negeri Surabaya, 2024)
In the implementation of a lesson, there are activities to transfer knowledge between teachers and students. During the learning process, teachers should not only provide material, but must develop and prepare teaching materials. In Indonesian learning, there are skills that students must master such as writing, reading, speaking, and listening skills. Therefore, teaching materials are needed to train students to acquire these skills. In reality, teachers only use teaching materials available from package books and thematic books provided by the government. Teachers hope that there will be more varied teaching materials to better support learning and more detailed material. This study aims to make teaching materials more varied and more detailed material so that students are more interested in understanding the material taught. This research uses a qualitative approach with content analysis methods. Then the data analysis techniques used are data reduction, data presentation, and conclusions. Based on the results of the analysis, various interrelated pieces of events have been found which are referred to as storylines. Then based on the time sequence, there are 29 subtitles using 7 forward flow patterns and 1 subheading whose presenter uses 1 mixed flow pattern. This proves that the forward plot is the dominant plot used in the fairy tale book. Based on the results of the analysis in the fairy tale book, it can be concluded that learning Indonesian using appropriate teaching materials can provide the latest alternative teaching materials.